ANALISIS CLUSTERING DENGAN K-MEANS UNTUK PENGELOMPOKKAN PENJUALAN PRODUK PADA HOTEL NEWTON - ., Event; Utnasari, Intan (LPPM Universitas Putera Batam, 2021)
Customer satisfaction is the main goal of many companies wants to achieve. One of the business fields that focus on customer satisfaction is hotel business. Apart from serving accommodation for customers, hotels also provide variety of products for sale. Inventory management is very important is hotel business because one of many ways to maintain customer satisfaction is by keeping stock so no items are empty when needed. In addition, a good inventory management will not let the company to experiences losses due to outdated inventory. Using data mining K-means clustering algorithm, we can group goods based on the salable goods and the less salable goods. This research aims to assist hotel Newton to improve their inventory management. Data that was used is sales that have been made which divided into 3 trimesters. Data also will be evaluated using RapidMiner application. The results obtained from the research are 3 clusters where the clusters consist of very salable goods, medium salable goods and not salable goods.